2017
DOI: 10.3389/fneur.2017.00365
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Blood Pressure Variability Is Associated with Poststroke Cognitive Impairment: A Prospective Cohort Study

Abstract: ObjectiveThe aim of this study was to investigate the relationship between blood pressure variability (BPV) and poststroke cognitive impairment (PSCI).MethodsSeven-hundred ninety-six patients with acute ischemic stroke were included in this study. Midterm BPV was evaluated by calculating the SD and coefficient of variation (CV, 100 × SD/mean) of systolic blood pressure (SBP) and diastolic blood pressure during the 7 days after stroke onset. Cognitive function was assessed using the Montreal Cognitive Assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…In short, 7 924 168 individuals over a follow‐up duration of 3 months to 22 years (mean age range, 54.3–84.4 years; 52.4% male) were included. Some studies required participants with specific comorbidities such as stroke or cardiovascular disease 23–28 . The remaining studies included the general population, and two studies by Haring (2019) 29 and Liu (2015) 30 excluded individuals with comorbidities, including diabetes mellitus, coronary heart disease, and/or stroke.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, 7 924 168 individuals over a follow‐up duration of 3 months to 22 years (mean age range, 54.3–84.4 years; 52.4% male) were included. Some studies required participants with specific comorbidities such as stroke or cardiovascular disease 23–28 . The remaining studies included the general population, and two studies by Haring (2019) 29 and Liu (2015) 30 excluded individuals with comorbidities, including diabetes mellitus, coronary heart disease, and/or stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies required participants with specific comorbidities such as stroke or cardiovascular disease. 23 , 24 , 25 , 26 , 27 , 28 The remaining studies included the general population, and two studies by Haring (2019) 29 and Liu (2015) 30 excluded individuals with comorbidities, including diabetes mellitus, coronary heart disease, and/or stroke. Among BPV measurement modalities, office BP was adopted in 15 (75%) studies, home BP in 4 (20%) studies, and ambulatory BP in 2 (10%) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above results, it is believed that chronic ischemia caused by hypertension may cause the interruption of the day and night changes in blood pressure through the damage of the brain's self-regulatory function, and then the blood pressure does not drop during sleep 43 . Previous studies 44,45 have found that systolic blood pressure variability is more predictive of cognitive dysfunction than systolic blood pressure. It's been reported that through community experiments that higher blood pressure variability is related to the decline in cognitive function of patients assessed by simple mental status examination 46 .…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with our findings, the incidence of cognitive impairment was reported to be 37.3% in a study of 209 patients with mild ischemic stroke ( 23 ). However, another prospective study recruiting 796 Chinese patients with ischemic stroke demonstrated that the prevalence of PSCI reached its peak (72%) 3 months after the stroke onset and decreased to 30.3% at 12 months ( 21 ). These results suggested an urgent need for an internationally agreed definition of PSCI.…”
Section: Discussionmentioning
confidence: 99%
“…Also, severe white matter lesions are mainly correlated with frontal lobe dysfunction, which was recognized as the consequence of damaged neural transmission and interneural connection ( 25 ). Similarly, Geng et al analyzed the data of a Stroke Registry database and observed that patients with PSCI had severe stroke severity as compared with those without PSCI ( 21 ). Therefore, the relationship between SAA and cognitive impairment might be caused by above factors.…”
Section: Discussionmentioning
confidence: 99%